GREEN HUMAN RESOURCE MANAGEMENT AND SUSTAINABLE ENVIRONMENTAL PERFORMANCE: ASSESSING THE MEDIATING ROLE OF ENVIRONMENTAL KNOWLEDGE AND CORPORATE SOCIAL RESPONSIBILITY - Ardeshir Bazrkar; Vahid Aramoon; Erfan Aramoon; Mehrdad Moradzad (Proceedings on Engineering Sciences, 2022)
The main purpose of this study was to investigate the impact of using green human resource management on sustainable environmental performance with respect to the mediating role of environmental knowledge and corporate social responsibility in the Iranian automotive industry. The present study was based on the purpose of an applied research and in terms of method was a descriptive -survey study. A questionnaire was used to collect research data. The statistical population of this study consisted of senior human resource managers of companies active in the automotive industry in Iran. The initial estimate showed that the total number of members of the statistical population is 143 people. After collecting data through a questionnaire, data analysis was performed using structural equation modeling. The results showed that the use of green human resource management methods has a positive and significant effect on the sustainable environmental performance of the companies under study. In addition, the sustainable environmental performance of the companies under study plays an effective mediating role. Therefore, it can be said that organizations can take steps to continuously and sustainable improvement of their environmental performance and increase the profitability of the organization by strengthening the strategies of green human resource management and paying special attention to the components of environmental knowledge and corporate social responsibility.